2012
DOI: 10.1371/journal.pone.0033505
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inflammatory Response to Inhaled Lipopolysaccharide Targeted Either to the Airways or the Alveoli in Man

Abstract: Endotoxin (Lipopolysaccharide, LPS) is a potent inducer of inflammation and there is various LPS contamination in the environment, being a trigger of lung diseases and exacerbation. The objective of this study was to assess the time course of inflammation and the sensitivities of the airways and alveoli to targeted LPS inhalation in order to understand the role of LPS challenge in airway disease.In healthy volunteers without any bronchial hyperresponsiveness we targeted sequentially 1, 5 and 20 µg LPS to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 52 publications
2
21
1
1
Order By: Relevance
“…(38) More recent studies with LPS challenge have shown a similar time course for LPS-induced inflammation. (39,40) As discussed above, the acute response (immediately post LPS challenge) of MCC in either study group may have been quite different from what we observed at 4 hr. Nevertheless, in this initial study on the effects of LPS exposure on MCC, we wanted to maintain similar timing to our previous studies so that we could compare the MCC and inflammatory responses at or near the same time post challenge.…”
Section: Discussioncontrasting
confidence: 64%
“…(38) More recent studies with LPS challenge have shown a similar time course for LPS-induced inflammation. (39,40) As discussed above, the acute response (immediately post LPS challenge) of MCC in either study group may have been quite different from what we observed at 4 hr. Nevertheless, in this initial study on the effects of LPS exposure on MCC, we wanted to maintain similar timing to our previous studies so that we could compare the MCC and inflammatory responses at or near the same time post challenge.…”
Section: Discussioncontrasting
confidence: 64%
“…30 In this study, we collected EBC using a capnograph-based method to determine the large airway and small airway or alveolar threshold. The initial separation is more precise for each patient using the plateau phase of the exhaled carbon dioxide concentration compared with a volume-based approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although DUOX expression is induced by proinflammatory cytokines, especially gamma interferon (36), the role of TLR4 ligands as triggers of H 2 O 2 production in the airways, as reported here, has not been studied extensively. Recently, Moller and colleagues (37) showed that in healthy human volunteers, the inhalation of micrograms of Salmonella LPS triggers a fast airway response, with a peak of H 2 O 2 production at 2 h poststimulation. According to the technique used, the authors concluded that H 2 O 2 production under these conditions is maximal in the airways, although the alveoli also contribute to the generation of ROS.…”
Section: Discussionmentioning
confidence: 99%